2012
DOI: 10.1258/la.2011.011092
|View full text |Cite
|
Sign up to set email alerts
|

An alternative method of endotracheal intubation of common marmosets (Callithrix jacchus)

Abstract: Endotracheal intubation was carried out in 11 common marmosets (Callithrix jacchus). A commercially available tilting stand and a Miller laryngoscope blade were used to visualize the larynx. Anaesthesia was induced with alphaxalone (10.6 + 1.6 mg/ kg intramuscularly, followed by 3.2 + 1.2 mg/kg intravenously). The diameter of the proximal trachea easily fitted an endotracheal tube made from readily available material (a 12 G 'over the needle' catheter). Once the tip of the endotracheal tube was at the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Despite the fact that there are no known published studies about the IM use of the newer alfaxalone formulation administered as a sole anaesthetic agent in cats, some studies reported clinical effects with alfaxalone ranging from good sedation to anaesthesia in different species of mammals (Thomas et al. ; Santos González et al. ; Giral et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that there are no known published studies about the IM use of the newer alfaxalone formulation administered as a sole anaesthetic agent in cats, some studies reported clinical effects with alfaxalone ranging from good sedation to anaesthesia in different species of mammals (Thomas et al. ; Santos González et al. ; Giral et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the IM administration of alfaxalone, alone or in combination with other drugs, has also been described in a number of species (Thomas et al. ; Hansen & Bertelsen ; Santos González et al. ) including cats (Grubb et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug dosages were chosen according to institute-wide practices and published references [37,38]. Our experience with the used protocols show that they were sufficient for minor invasive procedures, such as blood collection from the femoral vein, tuberculin testing, wound care, and radiography (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Visualization of the larynx is relatively straightforward using an appropriately-sized curved or straight blade, and for small primates, rodent intubation equipment can be used (Thomas et al, 2012b). Visualization of the larynx is relatively straightforward using an appropriately-sized curved or straight blade, and for small primates, rodent intubation equipment can be used (Thomas et al, 2012b).…”
Section: Intraoperative Monitoring and Supportmentioning
confidence: 99%